Effect of age on biomaterial-mediated in situ bone tissue regeneration. (15th September 2018) - Liu, Mengqian; Nakasaki, Manando; Shih, Yu-Ru Vernon; Varghese, Shyni
Graphical abstract: Abstract: Emerging studies show the potential application of synthetic biomaterials that are intrinsically osteoconductive and osteoinductive as bone grafts to treat critical bone defects. Here, the biomaterial not only assists recruitment of endogenous cells, but also supports cellular activities relevant to bone tissue formation and function. While such biomaterial-mediated in situ tissue engineering is highly attractive, success of such an approach relies largely on the regenerative potential of the recruited cells, which is anticipated to vary with age. In this study, we investigated the effect of the age of the host on mineralized biomaterial-mediated bone tissue repair using critical-sized cranial defects as a model system. Mice of varying ages, 1-month-old (juvenile), 2-month-old (young-adult), 6-month-old (middle-aged), and 14-month-old (elderly), were used as recipients. Our results show that the bio-mineralized scaffolds support bone tissue formation by recruiting endogenous cells for all groups albeit with differences in an age-related manner. Analyses of bone tissue formation after 2 and 8 weeks post-treatment show low mineral deposition and reduced number of osteocalcin and tartrate-resistant acid phosphatase (TRAP)-expressing cells in elderly mice. Statement of Significance: Tissue engineering strategies that promote tissue repair through recruitment of endogenous cells will have a significant impact in regenerative medicine. Previous studies from our group have shown that biomineralized materials containing calcium phosphate minerals can contribute to neo-bone tissue through recruitment and activation of endogenous cells. In this study, we investigated the effect of age of the recipient on biomaterial-mediated bone tissue repair. Our results show that the age of the recipient mouse had a significant impact on the quality and quantity of the engineered neo-bone tissues, in which delayed/compromised bone tissue formation was observed in older mice. These findings are in agreement with the clinical observations that age of patients is a key factor in bone repair.